2005
DOI: 10.1111/j.1600-0447.2004.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Trauma exposure and post‐traumatic stress disorder in the general population

Abstract: The conditional probability for PTSD varied as a function of trauma type, frequency and impact of the event, with increased rates associated with prevalent trauma exposure and higher perceived distress. The latter accounted for the gender effect, suggesting that gender differences in PTSD in part represent a generally greater vulnerability to stress in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
342
8
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(402 citation statements)
references
References 65 publications
41
342
8
11
Order By: Relevance
“…The prevalence of current PTSD in the Netherlands equals prevalence rates in the United States (3.5%; Kessler et al, 2005). Besides, consistent with previous epidemiological studies conducted in the United States (Breslau et al, 1998;Kessler et al, 1995Kessler et al, , 2005Resnick et al, 1993), Australia (Creamer, Burgess, & McFarlane, 2001), and Europe (Alonso et al, 2004;Frans et al, 2005;Perkonigg et al, 2000), the present study found high levels of PTSD after sexual and physical assault. Likewise, two studies that used the same measurement for stressful events show amazingly similar results in terms of occurrence (e.g., rank ordering of these events; Creamer et al, 2001;Kessler et al, 1995).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The prevalence of current PTSD in the Netherlands equals prevalence rates in the United States (3.5%; Kessler et al, 2005). Besides, consistent with previous epidemiological studies conducted in the United States (Breslau et al, 1998;Kessler et al, 1995Kessler et al, , 2005Resnick et al, 1993), Australia (Creamer, Burgess, & McFarlane, 2001), and Europe (Alonso et al, 2004;Frans et al, 2005;Perkonigg et al, 2000), the present study found high levels of PTSD after sexual and physical assault. Likewise, two studies that used the same measurement for stressful events show amazingly similar results in terms of occurrence (e.g., rank ordering of these events; Creamer et al, 2001;Kessler et al, 1995).…”
Section: Discussionsupporting
confidence: 93%
“…This manuscript was produced in close collaboration with the Centre for Psychological Trauma, Academic Medical Centre/De Meren, Department of Psychiatry, University of Amsterdam, the Netherlands. (1%) PTSD prevalence rates in Europe are lower than PTSD prevalence in the American studies (Alonso et al, 2004;Frans, Rimmo, Aberg, & Fredrikson, 2005;Perkonigg, Kessler, Storz, & Wittchen, 2000). However, findings across studies are hard to compare.…”
Section: In This Study the Lifetime Prevalence Of Stressful Events Amentioning
confidence: 93%
“…A majority of individuals will experience a potentially traumatic event during their lifetime (Frans, Rimmö, Aberg, & Fredrikson, 2005). For some individuals, these experiences are associated with the development of mental health problems such as depression (Mandelli, Petrelli, & Serretti, 2015), substance abuse and stress-related disorders such as posttraumatic stress disorder (PTSD; Arnberg, Bergh Johannesson, & Michel, 2013; Arnberg et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The second study did not account for trauma type . Trauma type is likely to play a confounding role in the relationship between child cognitive ability with PTSD risk, as measures of cognitive and scholastic ability have been found to predict the type of traumas a young person will subsequently experience (Breslau, et al, 2006;Storr, et al, 2007), and specific types of trauma are highly predictive of PTSD outcomes (Breslau, Chilcoat, Kessler, Peterson, & Lucia, 1999;Brewin, Andrews, & Valentine, 2000;Frans, Rimmo, Aberg, & Fredrikson, 2005). Additionally, individuals in this study were classed as trauma exposed only if they had experienced an acute reaction to the trauma (criterion A2).…”
Section: Introductionmentioning
confidence: 99%